ХАРАКТЕРИСТИКА ПРОИЗВОДИТЕЛЕЙ КАРПА (CYPRINUS CARPIO) КАПШАГАЙСКОГО НЕРЕСТОВО - ВЫРОСТНОГО ХОЗЯЙСТВА (Eurasian Journal of Ecology, 2016)
The descriptions of Kapshagai industry, modern conditions of female band are considered. Estimate of female crucian carp to receipt posterity. On basis of analysis reproduction recommend by bumping female band on this industry.